2006
DOI: 10.1037/0021-9010.91.6.1225
|View full text |Cite
|
Sign up to set email alerts
|

On the nature and importance of cultural tightness-looseness.

Abstract: Cross-cultural research is dominated by the use of values despite their mixed empirical support and their limited theoretical scope. This article expands the dominant paradigm in cross-cultural research by developing a theory of cultural tightness-looseness (the strength of social norms and the degree of sanctioning within societies) and by advancing a multilevel research agenda for future research. Through an exploration of the top-down, bottom-up, and moderating impact that cultural tightness-looseness has o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
910
1
5

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 811 publications
(958 citation statements)
references
References 197 publications
18
910
1
5
Order By: Relevance
“…In contrast, loose societies have fewer ecological and historical threats and can "afford" more deviant behavior. Although this research was conducted at the national level, there is increasing evidence that this critical contrast exists across different levels of analysis, differentiating, for example, organizations and industries (16). If tightness-looseness is a fundamental aspect of social systems, might it be an underlying principle that helps explain the wide variation that exists between the 50 US states?…”
mentioning
confidence: 99%
“…In contrast, loose societies have fewer ecological and historical threats and can "afford" more deviant behavior. Although this research was conducted at the national level, there is increasing evidence that this critical contrast exists across different levels of analysis, differentiating, for example, organizations and industries (16). If tightness-looseness is a fundamental aspect of social systems, might it be an underlying principle that helps explain the wide variation that exists between the 50 US states?…”
mentioning
confidence: 99%
“…This is probably due to the common understanding in the field that values are "among the building blocks of culture" (HOFSTEDE, 1980, p. 25). More recently, crosscultural researchers have raised doubts about the usefulness of the value concept (GELFAND; NISHII; RAVER, 2006). Empirical findings show mixed results with some studies supporting the explanatory power of values and other studies showing that values are not sufficient for understanding cultural differences (see GELFAND;NISHII;RAVER, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…Also, our study omitted a number of potentially relevant variables. For example, acculturation patterns may differ depending on whether the culture of the host society is tight or loose (Gelfand, Nishii and Raver 2006). It has been suggested that individuals from tight cultures may acculturate faster in loose cultures, while those from loose cultures may be slower to internalize values of culturally tight societies (Murphy and Anderson 2003).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%